PENGEMBANGANMODUL PEMBELAJARAN KIMIA BERORIENTASI CHEMOENTREPRENEURSHIP (CEP)PADA MATERI POLIMER KELAS XII SMA/MA - Arif Rahman Syafe'i; Jimmi Copriady; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop chemoentrepreneurship oriented chemistry learning modules (CEP) on polymer materials in class XII SMA / MA. This research was conducted at the Chemistry Education Campus of the Teaching and Education Faculty (FKIP) of RiauUniversity. When the research began in September-December 2019. This study uses a type of Research and Development (RnD) research with a 4D research model consisting of 4 stages namely Define, Design, Develop, and Disseminate. In this study, researchers only reached the development stage. Data collection instruments in the form of validation sheets and respondent sheets. Data analysis was performed using evaluation criteria for the level of validity, the level of practicality by the teacher and the level of attractiveness according to students. The results of the chemoentrepreneurship oriented chemistry learning module (CEP) on polymeric materials get a value of 92.35%. with valid criteria, the teacher's response as a user to the practicality of the module gets a value of 91.67% and the response of students as users to the attractiveness of the module gets a value of 90.67% with interesting criteria. Thus, chemoentrepreneurship oriented chemistry learning modules (CEP) in the grade XII SMA / MA polymer materials have been well developed and ready to be implemented on a broader scale.KeyWords: Module, chemoentrepreneurship(CEP), polymer